Validation of the Arabic and Tunisian Arabic version of the KINDL questionnaires for children with diabetes type 1. Issue 1 (1st January 2019) - Essaddam, Leïla; Ben Mansour, Asma; Ben Amor, Arwa; Ravens-Sieberer, Ulribe; Klein, Toni Maria; Ben Becher, Saayda
ABSTRACT: Aim : We aimed to validate the Arabic and Tunisian Arabic versions of diabetes- specific quality of life (QOL) instrument KINDL-R Diabetes Module for Tunisian children population with type 1 diabetes. Patients and methods : This a cross-sectional study to validate Arabic and Tunisian KINDL QOL instrument that we translate in literary and dialectal Arabic. Both forward and backward translations from the German version of KINDL QOL into Arabic version were performed. Our project received a GPED grant in August 2014. After the face validity of the Arabic version was established, it was then pilot-tested. Finally, the validity and reliability of the final version of the Arabic KINDL questionnaire were evaluated. Results : The KINDL-R Diabetes Module (DM) questionnaire of QOL was given to 212 persons : 108 children (aged 3–17 years) with T1DM and 104 parents. The Cronbach's alpha coefficients of the overall items and the main domains was about 0.7. The mean total score of the KINDL-R DM was 69, 56 Â ± 14, 01 in children aged 7–13 years, 59.93Â± 15.17 in children aged 13–17 years and 56.6Â± 9.9 in parents (higher scores indicate better QOL). The parents reported lower diabetes-specific HRQOL than the children themselves ( p  < 0.01).Emotional score was correlated to environment ( p  = 0, 03). Self-esteem was reported to environment ( p  = 0, 02) and mother's instruction level's ( p  = 0, 014). Conclusions : The KINDL-R Diabetes Module (DM) of QOL in literary and dialectal Arabic have sufficient acceptability, reliability and validity so as to be used for the purposes of a comparative in Tunisian and Arabic populations.